1995
DOI: 10.1115/1.2896008
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Plane Buckling of Fiber-Reinforced Thermoplastic Sheets Under Homogeneous Biaxial Conditions

Abstract: The mechanical behavior of fiber-reinforced composite thermoplastic sheets during forming processes is modelled as a viscous fluid with inextensibility and incompressibility constraints. Techniques of linear stability analysis are used to study the growth or decay of initial imperfections in plane sheets reinforced by two families of fibers subjected to biaxial strains. This theory delimits situations when buckles can be expected to form during forming operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The occurence of out-of-plane wrinkles is complex and has been studied by several researchers. For a given material, experimental studies reported that, amongst other factors, stress conditions induced by manufacturing boundary conditions, forming speeds, original blank dimensions and strain gradients play a role in their development [9,[25][26][27][28]. Considering simulation, Boisse et al also showed that the appearance of out-of-plane wrinkles is a global phenomenon which depends on boundary conditions and all types of strains and stiffness [14].…”
Section: Bending In Fe Forming Simulationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The occurence of out-of-plane wrinkles is complex and has been studied by several researchers. For a given material, experimental studies reported that, amongst other factors, stress conditions induced by manufacturing boundary conditions, forming speeds, original blank dimensions and strain gradients play a role in their development [9,[25][26][27][28]. Considering simulation, Boisse et al also showed that the appearance of out-of-plane wrinkles is a global phenomenon which depends on boundary conditions and all types of strains and stiffness [14].…”
Section: Bending In Fe Forming Simulationsmentioning
confidence: 95%
“…Defects such as fibre re-orientations and wrinkles (both in-plane and out-of-plane) are typically sought since they alter the mechanical performances of the final components [23]. Besides, out-of-plane wrinkles, also referred to as out-of-plane buckles, also affect the shape of the component [24,25]. The occurence of out-of-plane wrinkles is complex and has been studied by several researchers.…”
Section: Bending In Fe Forming Simulationsmentioning
confidence: 99%
“…This angle is the rotation that the fabric is subjected to, comparing to its initial direction. In the same period, Christie et al [34] has attributed the out-ofplane deformation to the effect of the compression (negative tension). When this compression occurs in a certain location of the fiber alignment, the fabric buckles in an out-of-plane deformation.…”
Section: A) Out Of Plane Deformationmentioning
confidence: 99%
“…Wrinkling may occur by buckling of the tows along the circumference of the hemisphere if the compressive force exceeds the critical buckling force. Several experimental studies [34][35][36][37][38][39] have reported that, amongst other factors, stress conditions induced by manufacturing boundary conditions, deforming rates, original blank dimensions and strain gradients play a role in their development. Boisse et al [26] have also shown that the formation of out-of-plane wrinkles is a global phenomenon dependent on process conditions (e.g., blank-holder pressure, and all types of strains and rigidities of the composite material).…”
Section: Global Deformation On Structural Level At Double Curved and mentioning
confidence: 99%